2013
DOI: 10.1021/ja311630a
|View full text |Cite
|
Sign up to set email alerts
|

Hyperstability and Substrate Promiscuity in Laboratory Resurrections of Precambrian β-Lactamases

Abstract: We report a sequence reconstruction analysis targeting several Precambrian nodes in the evolution of class-A β-lactamases and the preparation and experimental characterization of their encoded proteins. Despite extensive sequence differences with the modern enzymes (~100 amino acid differences), the proteins resurrected in the laboratory properly fold into the canonical lactamase structure. The encoded proteins from 2-3 billion years (Gyr)-old β-lactamase sequences undergo cooperative two-state thermal denatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
312
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(324 citation statements)
references
References 32 publications
9
312
2
1
Order By: Relevance
“…Thus, Ignisphera aggregans (12) and Pyrococcus horikoshii (13) exhibit optimal growth temperature of 92°and 98°C, respectively, whereas another organism isolated from a hydrothermal vent has been reported to grow at 121°C (14). Moreover, reconstructions of ancestral proteins, with amino acid sequences inferred from the sequences of their modern descendants, have been shown to be remarkably thermostable, with melting temperatures ∼30°C higher than those of proteins from their modern descendants (15,16).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
“…Thus, Ignisphera aggregans (12) and Pyrococcus horikoshii (13) exhibit optimal growth temperature of 92°and 98°C, respectively, whereas another organism isolated from a hydrothermal vent has been reported to grow at 121°C (14). Moreover, reconstructions of ancestral proteins, with amino acid sequences inferred from the sequences of their modern descendants, have been shown to be remarkably thermostable, with melting temperatures ∼30°C higher than those of proteins from their modern descendants (15,16).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
“…This information then can be used to engineer proteins with desired folding properties. ASR has already provided important insights into evolutionary trends in stability, specificity, and other biophysical properties (12)(13)(14)(15)(16)(17)(18)(19)(20).Previously, we used ASR to study the thermostability of the ribonuclease H (RNase H) family and demonstrated divergent trends in thermostability along mesophilic and thermophilic lineages (16). Here we examined the folding mechanism and associated rates of these reconstructed ancestral RNases H. The folding pathway of the two extant homologs, Escherichia coli RNase H (ecRNH) and Thermus thermophilus RNase H Significance Because protein folding is crucial to proper cellular function, there must be evolutionary pressures on how a protein achieves and maintains its folded structure.…”
mentioning
confidence: 99%
“…This information then can be used to engineer proteins with desired folding properties. ASR has already provided important insights into evolutionary trends in stability, specificity, and other biophysical properties (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has recently been used by researchers to reconstruct ancient α,β-hydrolases that were found to be more promiscuous than present enzymes [30]. In another study, the reconstruction of extinct β-lactamases afforded highly thermostable scaffolds [32]. As we were previously unable to identify enzyme-assisted hydrogen bond acceptors in esterases belonging to the α,β-hydrolases [26], we reasoned that analyzing alternative and existing enzyme folds would be a relevant second strategy for the identification of promiscuous esterase scaffolds that could serve as a starting point for further engineering (represented by the forward gear, Figure 1, left).…”
Section: Introductionmentioning
confidence: 99%